Recent Approaches to Chlorinating Reagents: An Overview - Deepak Sharma; Abha Chaudhary (Recent Developments in Science and Technology for Sustainable Future, 2024)
Chlorination is the most important substitution reaction in which one or more hydrogen atoms of organic compounds can be substituted by chlorine. The reaction provides the opportunity to synthesize chloro-derivative of organic substrates. The chloro-substituted compounds are valuable substrate in organic synthesis. The various reagents can be used to carry out chlorination reaction under specified reaction condition. The frequently used chlorinating reagents for carrying the chlorination smoothly under the different reaction condition are Chlorine gas with sunlight, sulfuryl Chloride in combination with peroxide, Chlorine in presence of Lewis acid such as anhyd. AlCl3 or anhyd. FeCl3, HCl or KCl with oxidant such as potassium peroxymonosulfate, stannic chloride and lead tetraacetate in DCM, sodium chlorite and trichloroacetic acid, acetyl chloride and ceric ammoniumnitrate. These reagents can be used either to form mono, di or poly chloro-derivaties of the organic substrate. Moreover, there is also the possibility of getting mixture of products. However, in some cases it becomes very important to control the reaction to monochlorinaton stage. So, there is always a necessity to search for chlorinating reagents which are safe to use and brings about the formation of only monochloroderivate as exclusive product. The substitution of hydrogen atoms of aromatic rings via chlorination can also take place readily and is very valuable reaction in organic synthesis and medicinal chemistry. The chloro-derivatives of aromatic compounds are very useful in production of fungicides, insecticides, dye and pharmaceutical. They served the role of additive in the preparation. The chloro-derivaties are also served as valuable starting material in various transformations for the synthesis of various organic compounds of biological and medicinal interest. Several methods for chlorination are reported in literature.